STUDENTS' CONCEPTUAL ERRORS ON HYDROSTATICS PRESSURE AND BOUYANCY THEORY - Firdausi Firdausi; Lia Yuliati; Parno Parno (Universitas Negeri Malang, 2019)
Abstract: The purpose of this study is to describe the conceptual error of high school students about the hydrostatic pressure and buoyancy. The design of this research was descriptive. Data were collected through multiple choice tests of four questions. The test was given to 64 high school students who had taken static fluid material. The test results were analyzed using percentage techniques. The results showed that the highest error experienced by students was in applying the concept of hydrostatic pressure (as much as 90.63% of students) followed by errors in analyzing the relationship between buoyancy force and the volume of objects immersed (as much as 87.50%). To sum up, two major misconceptions of students are about the notion that the hydrostatic pressure is influenced by the closed container and the volume of water and the buoyancy is proportional to depth and inversely proportional to the volume of the immersed object. Key Words: buoyancy, error, hydrostatic pressure Abstrak: Tujuan penelitian ini untuk mendeskripsikan kesalahan siswa SMA tentang konsep tekanan hidrostatik dan gaya apung. Desain penelitian ini adalah deskriptif. Data dikumpulkan melalui tes pilihan ganda sebanyak empat soal. Tes diberikan pada 64 siswa SMA yang telah menempuh materi fluida statik. Hasil tes tersebut dianalisis menggunakan teknik persentase. Hasil penelitian menunjukkan bahwa kesalahan tertinggi siswa adalah dalam menerapkan konsep tekanan hidrostatik (sebanyak 90,63% siswa) diikuti dengan kesalahan dalam menganalisis hubungan antara gaya apung dan volume benda tercelup (sebanyak 87,50%). Simpulan penelitian adalah kesalahan konsep tekanan hidrostatik yang dialami siswa, yaitu tekanan hidrostatik dipengaruhi oleh wadah tertutup dan volume air. Kesalahan konsep gaya apung yang dialami siswa, yaitu gaya apung sebanding kedalaman dan berbanding terbalik dengan volume benda yang tercelup. Kata kunci: gaya apung, kesalahan, tekanan hidrostatik